2006
DOI: 10.1080/17450390600679231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of partial dehulling of two- and six-row barley varieties on precaecal digestibility of amino acids in pigs

Abstract: Five barrows (German Landrace; initial BW 58 kg, final BW 80 kg) fitted with an ileo-rectal anastomosis were used to determine the effect of partial dehulling and addition of barley hulls of two- and six-row barley varieties on the precaecal digestibility (pD) of CP and amino acids. The following diets were provided according to a standardized diet formulation and tested in seven consecutive periods (repeated group-period design): two-row barley (TRB) + casein (C), dehulled TRB + C, TRB + C + 10% hulls, six-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
Section: Discussionsupporting
confidence: 84%
“…Thus, nutrient digestibility of barley in pigs can be substantially reduced (O'Connell et al, 2005). Moreover, less interaction between diet and digestive enzymes may result in increased specific ileal endogenous losses of CP and AA, as digesta viscosity inhibits sufficient interaction between (Chesson, 1993; Nyachoti et al, 2000;Jansman et al, 2002).The SID of CP and most AA estimated by regression analysis were in the range of SID values in barley reported in other studies (Hennig et al, 2006;Ige et al, 2010), and corresponded (95% confidence intervals) to SID values reported by NRC (2012) and AFZ et al (2000). (Eklund, 2006).…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In order to decrease the crude fibre (CF) in barley seeds the husk can be mechanically removed without knowledge how the nutritive value for pigs will be affected. Complete information about methodological aspects in digestibility determination of 18 proteinbound AA in the two barley varieties was recently presented (Hennig et al, 2006). The objective of the current contribution is to briefly describe how dehulling affect both the concentrations of gross AA and of ileal digestible AA.…”
Section: Introductionmentioning
confidence: 99%
“…1 and 2). (Sauer et al, 1977;Cousins et al, 1981;Sauer et al, 1981;Taverner et al, 1981;Walter et al, 1981;Adeola et al, 1986;Lin et al, 1987;Batterham et al, 1990;Herkelman et al, 1990;Haydon and Hobbs, 1991;Noblet et al, 1993;Adeola and Orban, 1995;Van Barneveld et al, 1998;Buraczewska et al, 1999;Reverter et al, 1999;Stein et al, 1999;O'Quinn et al, 2000;Cho et al, 2001;Fan and Sauer, 2002;Moeser et al, 2002;Yin et al, 2002;Fan and Sauer, 2003;Song et al, 2003;Mariscal-Landín et al, 2004;Snow et al, 2004;Kaufmann et al, 2005;Hennig et al, 2006;Muley et al, 2007;Opapeju et al, 2007;Pedersen et al, 2007;Lahaye et al, 2008;Nyachoti et al, 2010). c Ns: number of studies; Nt: number of ingredients in the model.…”
Section: Prediction Of Amino Acid Content From Crude Proteinmentioning
confidence: 98%